Functional and Taxonomic Diversity of Anaerobes in Supraglacial Microbial Communities - Pittino, Francesca; Zawierucha, Krzysztof; Poniecka, Ewa; Buda, Jakub; Rosatelli, Asia; Zordan, Simone; Azzoni, Roberto S; Diolaiuti, Guglielmina; Ambrosini, Roberto; Franzetti, Andrea (Microbiology spectrum, 2023)
Cryoconite holes are small ponds present on the surface of most glaciers filled with meltwater and sediment at the bottom. Although they are characterized by extreme conditions, they host bacterial communities with high taxonomic and functional biodiversity. Despite that evidence for a potential niche for anaerobic microorganisms and anaerobic processes has recently emerged, the composition of the microbial communities of the cryoconite reported so far has not shown the relevant presence of anaerobic taxa. We hypothesize that this is due to the lower growth yield of anaerobes compared to aerobic microorganisms. In this work, we aim at evaluating whether the anaerobic bacterial community represents a relevant fraction of the biodiversity of the cryoconite and at describing its structure and functions. We collected sediment samples from cryoconite holes on the Forni Glacier (Italy) and sequenced both 16S rRNA amplicon genes and 16S rRNA amplicon transcripts at different times of the day along a clear summer day. Results showed that a relevant fraction of taxa has been detected only by 16S rRNA transcripts and was undetectable in 16S rRNA gene amplicons. Furthermore, in the transcript approach, anaerobic taxa were overrepresented compared with DNA sequencing. The metatranscriptomics approach was used also to investigate the expression of the main metabolic functions. Results showed the occurrence of syntrophic and commensalism relationships among fermentative bacteria, hydrogenothrophs, and consumers of fermentation end products, which have never been reported so far in cryoconite. IMPORTANCE Recent evidence disclosed the presence of a potential niche for anaerobic microorganisms and anaerobic processes in supraglacial sediments (cryoconite), but a detailed description of the structure and functions of the anaerobic population is still lacking. This work used rRNA and mRNA sequencing and demonstrated that anaerobes are very active in these environments and represent a relevant albeit neglected part of the ecosystem functions in these environments.
Keywords: extremophiles; cryoconite; metatranscriptomics